Syntax a generative introduction - Carnie, Andrew 1969- (Introducing linguistics, 2021)
"Almost every preface to every syntax textbook out there starts out by telling the reader how different this book is from every other syntax textbook. On one hand, this is often the truth: each author shows their own particular spin or emphasis. This is certainly true of this textbook. For example, you'll be hard-pressed to find another textbook on Principles and Parameters syntax that uses as many Irish examples as this one does.. On the other hand, let's face facts. The basic material to be covered in an introductory textbook doesn't really vary much. One linguist may prefer a little more on binding theory, and a little less on control, etc. In this text, I've attempted to provide a relatively balanced presentation of most of the major issues and I've tried to do this in a student-friendly way. I've occasionally abstracted away from some of the thornier controversies, when I felt they weren't crucial to a student understanding the basics. This may make the professional syntactician feel that I've cut corners or laid out too rosy a picture. I did this on purpose, however, to give students a chance to absorb the fundamentals before challenging the issues. This was a deliberate pedagogical choice. I'm well aware that sometimes I've glossed over controversies, but I think a student has to learn the basics of how the system works before they can seriously critique and evaluate the model. This is a textbook, not a scholarly tome, so its aim is to reach as many students as possible. The style is deliberately low-key and friendly. This doesn't mean I don't want the students to challenge the material I've presented here. Throughout the book, you'll find grey "textboxes" that contain issues for further discussion or interesting tidbits. Many of the problem sets also invite the student to challenge the black and white presentation I've given in the text. I encourage instructors to assign these, and students to do them, as they form an important part of the textbook. Instructors may note that if a favorite topic is not dealt with in the body of the text, a problem set may very well treat the question."